Heat Standard Across Different Workloads in Nepal - Mishra, A. K. (GS WOW: Wisdom of Worthy Research Journal, 2024)
This study aims to recommend Threshold Limit Values (TLVs) for occupational heat exposure in Nepalese industries. The analysis is based on the evaluation of heat stress levels in various sectors in Nepal, including the Tea Processing (Orthodox) sector and the Brick sector. The study also reviews international standards for occupational heat exposure limits and existing heat stress levels of Nepalese industries. The recommended TLVs are based on the analysis of heat stress levels in different sectors in Nepal and are within the range of recommended values by international organizations such as ACGIH. Implementing these TLVs will help ensure a safer working environment for workers in Nepal, particularly in sectors that experience heavy workloads.